PERAN KOMUNIKASI INTERPERSONAL ANTARA USTADZ DAN SANTRI DALAM PEMBENTUKAN KARAKTER SANTRI DI PONDOK PESANTREN MODERN AL-AZHAR GRESIK - Muhammad Kavien Maulana Muchtar; Kasuwi Saiban; Umi Salamah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the role of interpersonal communication between ustadz and santri in character formation at Pondok Pesantren Modern Al-Azhar Gresik. The research uses a qualitative descriptive approach with data collected through in-depth interviews, direct observation, and documentation. Data analysis employed the Miles, Huberman, and Saldana interactive model. The findings indicate that interpersonal communication between ustadz and santri plays a significant role in shaping santri character through three main processes: first, communication takes place not only in the classroom but across all daily activities; second, an intimate communication atmosphere makes santri more open and receptive; third, ustadz role modeling constitutes a powerful form of non-verbal communication. The roles performed by ustadz include acting as character guide and companion, as moral exemplar, and as a vehicle for instilling character values. The implications of this interpersonal communication are reflected in the formation of santri who possess noble character (akhlakul karimah), high spiritual awareness, and the ability to behave positively in everyday life.